ASME 2011 Summer Bioengineering Conference, Parts a and B 2011
DOI: 10.1115/sbc2011-53443
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Histologic System for 3D Histomorphometry of the Mouse Knee

Abstract: Osteoarthritis (OA) is a degenerative joint disease that is a leading cause of adult pain and disability in Western countries1. Clinically, several structural features of the joint are important in diagnosis, prognosis and evaluation of treatment efficacy, e.g. cartilage volume, homogeneity and joint space narrowing2,3. In animal models of OA, structural features such as bone defects and cartilage changes are commonly investigated using histomorphometry, a technique that uses stereological point counting and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this study, we sought to image mouse articular cartilage in 3D and obtain morphological information on this tissue using a customized device for high‐throughput robotic histology. The use of automated systems for high‐resolution, 3D histological imaging is becoming increasingly important to assess experimental models of pathology (Tsuchiya & Yamada, ) and newer systems can now achieve full automation on serial sectioning and imaging (Kazakia et al, ; Murienne et al, ; Wilson et al, ) which previous systems did only by semi‐automated approaches (Hashimoto, Kusakabe, & Ishikawa, ). Using the 3D histocutter, we successfully demonstrated that, in the absence of any staining and purely based on tissue autofluorescence, articular cartilage and subchondral bone can be imaged in 3D at high‐resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we sought to image mouse articular cartilage in 3D and obtain morphological information on this tissue using a customized device for high‐throughput robotic histology. The use of automated systems for high‐resolution, 3D histological imaging is becoming increasingly important to assess experimental models of pathology (Tsuchiya & Yamada, ) and newer systems can now achieve full automation on serial sectioning and imaging (Kazakia et al, ; Murienne et al, ; Wilson et al, ) which previous systems did only by semi‐automated approaches (Hashimoto, Kusakabe, & Ishikawa, ). Using the 3D histocutter, we successfully demonstrated that, in the absence of any staining and purely based on tissue autofluorescence, articular cartilage and subchondral bone can be imaged in 3D at high‐resolution.…”
Section: Discussionmentioning
confidence: 99%
“…While the rotary microtome in the cutting unit removes thin sections that are discarded by air puffers, the high‐resolution camera images the surface. A sequential stack of images is recorded in the computer and acquisition using multiple fluorescent channels is also possible (Andrikakou et al, ; Murienne et al, ; Tang et al, ).…”
Section: D Robotic Histologymentioning
confidence: 99%
See 1 more Smart Citation